Regreening, restoring, and reconnecting a southwestern wetland ecosystem – the Zeedyk wetland - Roy E. Petrakis; Laura M. Norman; Maryann McGraw; Steve Carson; Craig Sponholtz; Cameron Weber; William D. Zeedyk (Remote Sensing Applications: Society and Environment, 2026)

Multiple and contrasting pressures determine intraspecific phytochemical variation in a tropical shrub - Andrea E. Glassmire; Walter P. Carson; Angela M. Smilanich; Lora A. Richards; Christopher S. Jeffrey; Craig D. Dodson; Casey S. Philbin; Garcia L. Humberto; Lee A. Dyer (Oecologia, 2023)

Phase II MS4 challenges: moving toward effective stormwater management for small municipalities - Leslie Rieck; Craig Carson; Robert J. Hawley; Madison Heller; Mike Paul; Mateo Scoggins; Mel Zimmerman; Robert F. Smith (Urban Ecosystems, 2022)
Federal regulations for municipal separate storm sewer systems (MS4s) in the United States have been in place since 1990 as part of the Nation Pollutant Discharge Elimination System (NPDES), aiming to reduce sediment and pollutant loads originating from urban areas. However, small-municipality (Phase II) MS4s frequently grapple with several challenges, resulting in a lack of stakeholder buy-in and actionable stormwater management plans. We identify five common challenges concerning MS4 requirements based on literature review, professional experience, and feedback solicited from stakeholders, municipal managers, and fellow professionals and offer real-world examples of efficient, effective MS4 frameworks and/or solutions. The five challenges are summarized as beliefs that: (1) agricultural land use is the largest pollutant contributor and the root cause of pollution problems; (2) stormwater management only benefits downstream communities; (3) large, expensive projects are required to comply with regulations; (4) maintenance, monitoring, and inspection of best management practices (BMPs) is overwhelmingly complex and expensive; and (5) a lack of direct funding makes complying with regulations an impossible task. These challenges are universal in nature for Phase II MS4 permittees and can create real barriers for effective stormwater management. However, we found many examples of methods or techniques to effectively address these five specific challenges, making them well-suited and important for discussion. BMPs can create tangible improvements for surrounding communities (e.g., reduced streambank erosion and flooding), and improved understanding of the structure and options within the MS4 program will help small municipalities make informed choices about management plans.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Variation in RTN3 and PPIL2 Genes Does not Influence Platelet Membrane β-Secretase Activity or Susceptibility to Alzheimer’s Disease in the Northern Irish Population - Robyn Carson; Amy Jayne McKnight; Stephen Todd; Wei Wei Liu; Shirley Heggarty; David Craig; Bernadette McGuinness; G. Brent Irvine; A. Peter Passmore; Janet A. Johnston (NeuroMolecular Medicine, 2009)

Genetic Variation in the α7 Nicotinic Acetylcholine Receptor is Associated with Delusional Symptoms in Alzheimer’s Disease - Robyn Carson; David Craig; Dominic Hart; Stephen Todd; Bernadette McGuinness; Janet A. Johnston; Francis A. O’Neill; Craig W. Ritchie; A. Peter Passmore (NeuroMolecular Medicine, 2008)

BACE1 Polymorphisms Do Not Influence Platelet Membrane β-secretase Activity or Genetic Susceptibility for Alzheimer’s Disease in the Northern Irish Population - S. Todd; A. J. McKnight; W. W. Liu; R. Carson; S. Heggarty; B. McGuinness; G. B. Irvine; D. Craig; A. P. Passmore; J. A. Johnston (NeuroMolecular Medicine, 2008)